ANALISIS PENGARUH KEUNGGULAN CITRA MEREK, KEUNGGULAN KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI HELM INK (Survei pada Mahasiswa Fakultas Ekonomi Universitas Slamet Riyadi Surakarta) - Retno Susanti, Ratih Sapitri, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2016)
This study aims to (1) analyze the significance of the effect of the advantages of brand image to buying interest helmet products INK; (2) analyze the significance of the influence of superior quality products to the buying interest helmet products INK; (3) analyze the significance of the effect on the price of buying interest INK helmet products, and (4) analyzing the dominant variable influence on buying interest helmet products INK. The population throughout the Faculty of Economics University of Slamet Riyadi Surakarta who have INK helmet numbered 100 students and as respondents. Test instrument using validity and reliability test. Classic assumption test using the test: Multicolinearity, Heteroskidastity, autocorrelation and normality. Data analysis techniques: multiple linear regression, t-test, F, and the coefficient of determination. The results showed no significant effect superiority of brand image to buying interest helmet products INK, no significant effect superior quality products to the buying interest helmet products INK, no significant effect of price to purchase interest helmet products INK, superior brand image dominant influence on interest buy products INK helmet.Keywords: brand image of excellence, superior quality products, prices, interest in buying products helm INK